(untitled) (Texas Journal of Medical Science, 2022)
Surgical treatment includes rapid activation of the patient, restoration of his ability to stand up, self-care (will), and trophic changes in the skin (bed sores), thromboembolic complications, pulmonary bronchial infection, decompensation of previously compensated organ failure reduces the risk of developing complications. Dystrophic-degenerative diseases also have a negative impact on elderly patients